APPLICATION OF THE PRINCIPLE OF GOOD FAITH OF BUSINESS ASSOCIATIONS AS A REALIZATION OF CONSUMER RIGHTS IN AGREEMENTS BUY AND BUY ONLINE VIA TIKTOK SHOP ACCOUNT - AGUSTINUS ARUAN; Abd Thalib; M. Musa; Thamrin S (International Conference On Law And Social Sciences, 2024)
The principle of good faith can be interpreted as meaning that each party in an agreement to be agreed has an obligation to provide as complete information or information as possible which can influence the other party's decision regarding whether to agree to the agreement or not. Article 9 of Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) also requires business actors to provide complete and correct information. However, until now there are still many online business people who do not know about their obligations as business actors. There are still many online shops such as Tik Tok Shop that do not include addresses as a form of information to consumers and have unclear descriptions of the goods on offer, which could potentially cause losses for consumers when purchasing them. The purpose of writing this article is to find out how the Principle of Good Faith of Business Actors is implemented in Online Buying and Selling Agreements Reasons for Not Fulfilling the Principle of Good Faith in Implementing Online Sales and Purchase Agreements via Tiktok Shop Accounts. This type of research is normative legal research. The data source comes from secondary data which is divided into three types of data, namely primary legal materials, secondary legal materials and tertiary legal materials.